EFEKTIFITAS PENERAPAN ATURAN PILKADA SERENTAK 2020 DALAM KONDISI DARURAT PENANGANAN PENCEGAHAN PENYEBARAN CORONA VIRUS DISEASE 19 (COVID-19) - Siti Nani Aisyah (UIN Sunan Gunung Djati Bandung, 2020)
Public safety fundamental must be prioritized above the fundamental of election. The implementation of quality Regional Elections does not go straight with the results of quality leaders, for this reason public safety priorities in the Election 2020 in the conditions of the Covid-19 pandemic must be a priority. Based on this, the author intends to discuss the effectiveness of the implementation of Regional Election regulations in the pandemic conditions of the Covid-19. This study uses a qualitative method with a statue approach. If the results of multi-aspect simulations and predictions of pandemic’s control will improve by the end of 2020, the Regional Election should be postponed by mid-2021, and for some Head Regional whose term of office has expired, they will be appointed as functionary.